Profile of medical information sought by Polish travelers - Korzeniewski, Krzysztof (Family Medicine & Primary Care Review, 2016)
Background. International travel is growing constantly throughout the world, with an annual growth rate estimated at 4%. According to the United Nations World Tourism Organization, the number of international travelers reached 1.184 billion in 2015. Owing to unprecedented interest in foreign travel, including travel to tropical countries, it is important for travelers to gain access to information on the most prevalent health hazards in destination countries and on recommended prevention measures. Objectives. This article describes the profile of medical information sought by Polish travelers on a website run by the Department of Epidemiology and Tropical Medicine, Military Institute of Medicine (Gdynia, Poland). Material and methods. The retrospective study was based on the statistical analysis of the number of visits to www.medycynatropikalna. pl between 2012 and 2015 and in the individual months of 2015. Results. Analysis shows a significant increase in the number of visits to the travel medicine website, from 76,369 in 2012 to 456,613 in 2015. In 2015, the website was most often visited in January, June, and the October–December period. Internet users most commonly sought information on vaccinations before going to Thailand, India, Kenya, anzania/Zanzibar, as well as on illnesses like yellow fever, HIV/AIDS, typhoid fever, and Ebola hemorrhagic fever during its outbreak in West Africa. Conclusions . The considerable increase in the number of visits to w.medycynatropikalna.pl in recent years is evidence of a growing interest in travel medicine and a greater awareness of health among travelers. The majority of website searches concerned Asia, Africa, and Central America, which may suggest a growing interest in travel to tropical countries.